Are consumers myopic? Evidence from handset and mobile services choices - Ambre Nicolle (International Telecommunications Society (ITS), 2016)
This paper estimates a discrete choice model for combination of mobile tariffs and handsets using a crosssection of 11,000 new customers from a European telecommunications carrier. It mainly focuses on the valuation of tariff price, handset subsidy and price of the handset. On the one hand, a significant evolution is observed over time. Indeed, important changes on the supply side are observed, mainly in the mobile service market but also in the retailing market. On the other hand, age of consumers also influences in a wide extent consumers valuation of services and handset. Accounting for this heterogeneity, the model enables to estimate a measure for myopia occurring when consumers are trading-off price of the tariff and upfront cost of the handset. If evidence of myopia is shown for the whole time period considered (Q4 of 2011- Q4 of 2014), its magnitude tends to decrease significantly since the end of 2012. This effect is mainly due to the take-off of sim-only contracts, emergence of cheaper handsets and improved quality of information provided to consumers.
Keywords: 330; Handset subsidy; Consumer myopia; Heterogeneous preferences